Nurraysa Beauty Skincare / Nur Atirah Abdullah - Abdullah, Nur Atirah (2020)
Nurraysa (Nurraysa Global Sdn Bhd) or formerly known as Nurraysa Beauty is a Muslim-made beauty product company founded by Mrs. Nur Aini Zolkepeli. Nurraysa's products are free from harmful chemicals in accordance with its Mesra Insurance theme where they are easy to wash and can carry prayers. Starting with just RM500 capital, the Nurraysa brand now has thousands of agents with over 100 billboards installed along highways throughout the peninsula of Malaysia With the aim of creating a congregation business opportunity, Nurraysa founder, Mrs Aini Zolkepeli is committed to providing guidance to Nurraysa's stockists & agents so they can make 6 figures a month! Thankfully, at the age of 23 Mrs. Nur Aini has made over RM1 million a month and helped over 5,000 people earn and raise 5 million in 2016 & 13 million in 2017. Nurraysa has appeared in newspapers and various media such as TV3's Main Bulletin, Assalamualaikum TV9, from 2014 to the present.